Relative Young's modulus and thermal conductivity of isotropic porous ceramics with randomly oriented spheroidal pores – Model-based relations, cross-property predictions and numerical calculations. Issue 11 (September 2018) - Pabst, Willi; Uhlířová, Tereza; Gregorová, Eva; Wiegmann, Andreas
Abstract: Based on computer-generated digital microstructures with spherical or spheroidal pores (isolated or overlapping) of aspect ratio 1 (spherical), 10 (prolate) and 0.1 (oblate), the relative thermal conductivity and Young's modulus is numerically calculated and compared to predictions based on generalized effective medium approximations (EMAs) and a recently proposed generalized cross-property relation (CPR). It is shown that, when the aspect ratio is known, generalized power-law and exponential relations provide satisfactory predictions of these two properties without the use of empirical fit parameters. The maximum deviation of these two types of EMA predictions from the true values ranges from −0.04 to +0.06 relative property units (RPU) for the power-law relation and from −0.02 to −0.10 RPU for the exponential relation. However, the generalized CPR results in an even higher accuracy of the predictions, with maximum deviations smaller than 0.01 RPU for the Young's modulus when the thermal conductivity is known.